Generating Embedded Reinforcement in Hexahedral Elements for Concrete Simulation - Markou, George; Papadrakakis, Manolis (My University, 2010)
In this paper an automatic procedure for the generation of embedded steel reinforcement inside hexahedral finite elements is presented. The automatic mapping of the entire reinforcement network inside the mesh of the hexahedral concrete elements is performed by using the end-point coordinates of the reinforcement, which are provided through the graphical environment of the commercial code Femap for finite element analysis. The proposed method alleviates the task of generating the embedded rebar mesh when dealing with arbitrary reinforcement geometry and treats the numerical problem of having a reinforcement located on the boundary face of two adjacent hexahedral elements. By introducing a geometrical constraint, this procedure decreases significantly the computational effort of generating the input data for the embedded rebar elements in three-dimensional finite-element analysis, particularly when dealing with large-scale reinforced concrete structures. The computational robustness and efficiency of the proposed mesh generation method, are shown through numerical experiments.